2018
DOI: 10.1016/j.hpb.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Resection of gallbladder remnants after subtotal cholecystectomy: presentation and management

Abstract: Redocholecystectomy (RC) for gallbladder remnants has been detailed in case reports, but no sizable North American series have been presented. These results illustrate a drawback to the reconstituting technique of SC. RC effectively resolves symptoms but requires adherence to safe principles of cholecystectomy and is one indication for an open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
0
29
0
3
Order By: Relevance
“…11 With increasing availability and use of high resolution axial imaging modalities such as computed tomography and magnetic resonance imaging, it is increasingly recognized that these symptoms may be attributable to a remnant gallbladder. In two case series presented by Singh et al 7 and Concors et al, 8 diagnosis of the remnant gall bladder is often challenging. Furthermore, Singh et al identified that reporting and disclosure of a subtotal cholecystectomy was absent 71% of these cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 With increasing availability and use of high resolution axial imaging modalities such as computed tomography and magnetic resonance imaging, it is increasingly recognized that these symptoms may be attributable to a remnant gallbladder. In two case series presented by Singh et al 7 and Concors et al, 8 diagnosis of the remnant gall bladder is often challenging. Furthermore, Singh et al identified that reporting and disclosure of a subtotal cholecystectomy was absent 71% of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of performing a cholangiogram is often debated, citing the need to perform a ductotomy as the source of bile duct injury. 8 However, the cholangiogram provides the benefit of confirming duct anatomy, including the length of the cystic duct, and identifying duct calculi, including the cystic duct. In this cohort, the trend of practice is to perform a cholangiogram as standard, demonstrated by the increasing rate of cholangiogram over the time period to 73%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difficult gallbladder is a scenario caused by the inflammation, difficult exposure, Mirizzi syndrome, and cirrhosis of the liver. These are the situations where the surgeons often adapt the "bail-out" strategy such as subtotal cholecystectomy (3-8% of total cholecystectomies), so as to avoid iatrogenic complications to the bile duct and bowel [2]. On the contrary, the subtotal cholecystectomy does have the risk of increased bile leak from the stump and rarely a residual gallbladder (GB) [3].…”
Section: Introductionmentioning
confidence: 99%